2020
DOI: 10.2147/cia.s266722
|View full text |Cite
|
Sign up to set email alerts
|

<p>Association Between Bone Mineral Density and Lipid Profile in Chinese Women</p>

Abstract: Atherosclerotic cardiovascular disease may share the risk factors for low bone mineral density (BMD), one of which is dyslipidemia. The association between serum cholesterol and BMD remains controversial. Thus, the correlation between serum lipids and BMD in women was explored in the current study. Materials and Methods: This cross-sectional study included 1116 Chinese female participants. Serum samples were collected to evaluate total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 42 publications
2
50
0
2
Order By: Relevance
“…For example, in Iranian women, Maghbooli et al found that HDL-C levels displayed an inversely correlation with BMD in postmenopausal women with vitamin D deficiency [ 17 ]. Zhang et al demonstrated that HDL-C exhibited a negative association with BMD in Chinese women above 50 years of age [ 18 ]. Makovey et al observed a modest inverse relationship between hip BMD and HDL-C in postmenopausal women [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Iranian women, Maghbooli et al found that HDL-C levels displayed an inversely correlation with BMD in postmenopausal women with vitamin D deficiency [ 17 ]. Zhang et al demonstrated that HDL-C exhibited a negative association with BMD in Chinese women above 50 years of age [ 18 ]. Makovey et al observed a modest inverse relationship between hip BMD and HDL-C in postmenopausal women [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maghbooli et al found that HDL-C exhibited an inverse correlation with BMD in postmenopausal Iranian women with vitamin D deficiency [ 17 ]. Zhang et al observed that HDL-C displayed a negative correlation with lumbar spine BMD in Chinese women [ 18 ]. Conversely, Cui et al suggested that there was no association between HDL-C levels and BMD values at any sites in pre- and postmenopausal subjects [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…A survey of Chinese people showed that elevated levels of serum high-density lipoprotein cholesterol (HDL-C) led to higher risk of osteoporosis, but a higher HDL-C level was favourable for cardiovascular diseases [ 41 ]. Another study indicated that femoral neck BMD in postmenopausal women was positively correlated with low-density lipoprotein cholesterol (LDL-C) and negatively correlated with HDL-C [ 42 ]. Some clinical data from other populations also support this view [ 43 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maghbooli et al found a negative correlation between HDL-C and BMD in postmenopausal Iranian women with vitamin D de ciency [14]. Zhang et al observed that HDL-C was negatively associated with lumbar spine BMD in Chinese women [15]. Conversely, Cui et al suggested that HDL-C level was not associated with BMD values at any of the sites in pre-and post-menopausal subjects [16].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies also explored the association between HDL-C and BMD[14][15][16][17]. For example,Maghbooli et al found in Iranian women that HDL-C levels were negatively correlated with BMD in postmenopausal women with vitamin D de ciency [14].…”
mentioning
confidence: 99%